Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1111/j.1528-1157.1989.tb05820.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of ACC‐9653 (Phenytoin Prodrug)

Abstract: ACC-9653, the disodium phosphate ester of 3-hydroxymethyl-5,5-diphenylhydantoin, is a prodrug of phenytoin with advantageous physicochemical properties. ACC-9653 is rapidly converted enzymatically to phenytoin in vivo. ACC-9653 and phenytoin sodium have equivalent anticonvulsant activity against seizures induced by maximal electroshock (MES) in mice following i.p., oral, or i.v. administration. The ED50 doses were 16 mg/kg for i.v. ACC-9653 and 8 mg/kg for i.v. phenytoin sodium. ACC-9653 and phenytoin sodium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 18 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Fosphenytoin is a prodrug that is enzymatically converted to PHT by phosphorylases present in most tissues and blood (16,17). Shith et al (18) reported that on an , equimolar basis PHT and fosphenytoin have equivalent anticonvulsant activity against seizures induced by maximal electroshock in mice. Moreover, fosphenytoin is freely soluble in aqueous solutions (1 9) and can therefore be administered in peripheral tissues with minimal discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Fosphenytoin is a prodrug that is enzymatically converted to PHT by phosphorylases present in most tissues and blood (16,17). Shith et al (18) reported that on an , equimolar basis PHT and fosphenytoin have equivalent anticonvulsant activity against seizures induced by maximal electroshock in mice. Moreover, fosphenytoin is freely soluble in aqueous solutions (1 9) and can therefore be administered in peripheral tissues with minimal discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16] Recrystallization from DMF/water afforded 14 g (50%): mp 254-257°C dec (lit. 15 10.14 g of potassium hydroxide (178 mmol), and 2.5 g of PEG 600 were heated at 100°C for 2 h in a twophase system consisting of 200 mL of water and 200 mL of 1-butanol. After cooling, the mixture was filtered and acidified with acetic acid to give a precipitate, which was washed with water and recrystallized X Abstract published in Advance ACS Abstracts, September 1, 1996. to give 16.5 g (59%).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In order to overcome this drawback, several phenytoin prodrugs, mostly esters of 3-(hydroxymethyl)phenytoin, have been investigated. [6][7][8][9] Fosphenytoin (ACC-9653) 10 is currently under clinical investigation for the treatment of the status epilepticus. 11 As an alternative approach, structural analogues of phenytoin such as 5,5-diphenyl-2-thiohydantoin, 12 4,4-diphenyl-1,2,5-thiazolidin-3-one 1,1-dioxide, 13 and 5,5-diphenyl-2-iminohydantoin 14 have been prepared but showed only a low anticonvulsant activity in animal models if any activity was noted at all.…”
Section: Introductionmentioning
confidence: 99%
“…1 FOS is a water-soluble, disodium phosphate ester of phenytoin that can be administered parenterally without a propylene glycol vehicle. 2 Thus, FOS is safer to administer than phenytoin because propylene glycol likely causes the hypotension and cardiac arrhythmias reported in patients who received phenytoin. 3 Indeed, it is generally accepted that FOS is associated with fewer significant adverse cardiovascular effects than phenytoin.…”
Section: What Is Known and Objectivementioning
confidence: 99%